Progressive multifocal leukoencephalopathy in multiple myeloma. (18th December 2022) - Hoeynck, Brian W.; Cohen, Adam D.; Stadtmauer, Edward A.; Susanibar‐Adaniya, Sandra P.; Vogl, Dan T.; Waxman, Adam J.; Bardsley, Mark; Le, Samantha; LaMaestra, Lexis; Garfall, Alfred L.
Abstract: Progressive multifocal leukoencephalopathy (PML) is a rare and often fatal demyelinating disease of the central nervous system caused by reactivation of the JC virus in the context of immune suppression such as HIV, malignancy, and certain immunomodulatory medications. PML has been reported only rarely in multiple myeloma patients, and its presenting features and natural history in this population are not well known. We describe six cases of PML among multiple myeloma patients treated at our institution between 2013 and 2022, including two that developed on or shortly after treatment with recently developed BCMA‐directed immunotherapies.